Knez Pokrajac Oliverovic (A Contribution to his identification) - Pekić, Radmilo (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
One of the well known medieval epitaphs of Bosnia and Herzegovina is located on the medieval tombstone – a stećak located in countryside Vrpolje in Ljubomir near Trebinje. The epitaph signifies grave site of prince Pokrajac Oliverovic, subject of Duke Sandal Hranic, about whom is known nothing except that.Based off of Dubrovnik resources it has been established that in the Ljubomir were inhabited Vlachs Burmaz from which stood out katun Dermanovic, named after theirs elder katunar Derman. His heir was Oliver Dermanovic. In following period in Dubrovnik resources is mentioned Pokrajac Oliverovic Vlach Dermanovic, nobleman from Ljubomir, most likely son and heir of already mentioned Oliver Dermanovic. Time and place of his life testify to be about Princeps Pokrajac Oliverovic, subject of Duke Sandal Hranic, who was buried in Vrpolje in Ljubomir, whose medieval monument- a stećak with imposing epitaph has been preserved to this day. Pokrajac Oliverovic died between 1429 and 1435. In following time in Ljubomir is mentioned nobleman who bore a patrimonial surname Pokrajchic after his father.
Keywords: Pokrajac Oliverovic; prince; stećak; epitaph; Ljubomir